Tracking Data for Chains as strong as the weakest link: remote assessment of aquatic resource use on spring migration by Bewick's Swans - Nuijten, Rascha J.M.; Nolet, Bart A. (Physiological and Biochemical Zoology, 2021)
,"timestamp","tag.ID","longitude.decimal.degree.","latitude.decimal.degree.","height.above.mean.sea.level","ground.speed","heading","location.error.numerical","GNSS.satellite.count","GNSS.satellite.visible","GNSS.maximum.signal.strength","GNSS.fix.type","GNSS.time.to.fix","year","month","rowID","watersensor","watersensorfreq"